Early and maintained application of the secretion of Cryptomphalus aspersa (SCA) 40% improves cutaneous healing after ablative fractional laser in skin aging. (24th September 2020) - Fernandez‐Gonzalez, Pablo; Vitale, Maria; Truchuelo, M. Teresa
Abstract: Background: Ablative fractional laser generates a regulated skin damage, which secondarily improves skin aging. Aims: The main objective of the present study was to figure out if the adverse effects induced by laser and the skin recovery could improve with the application of a cosmetic product based on the secretion of Cryptomphalus aspersa (SCA). Patients/Methods: A prospective double‐blind controlled study with vehicle in 10 patients with skin aging. The patients received one session of fractional ablative CO2 laser, and the formulation with SCA 40% was applied immediately and maintained throughout the 21‐day duration of the study. The active treatment (SCA) was applied to one hemifacial area and vehicle to the other, and the patient acting was her own control. Clinical evaluations, dermoscopy, photography, and other parameters like cutaneous hydration, elasticity, and wrinkles were evaluated. In addition, the severity of the adverse effects was evaluated. Results: Significant greater decrease in the density of microcolumns produced by laser was detected on the active‐treated side, indicating greater and faster postprocedure recovery compared to the vehicle‐treated side. In addition, side effects were reduced and some antiaging effects were more apparent on the side treated with SCA 40%. Conclusion: SCA 40% applied immediately after ablative laser, and during the next days, it can accelerate laser‐induced damage regeneration. In addition, SCA improves the cosmetic outcome after laser application.